Study on the Fairness Measurement of Regional Innovation Resource Allocation and Its Spatial Correlation Features - Song Liang, Xuerui Lv (Forest Chemicals Review)
The imbalance of China’ s economic and social development leads to significant unfairness in the regional innovation resource allocation, which not only leads to excessive innovation polarization and insufficient diffusion in the first developing areas, but also seriously inhibits the late developing advantage potential of the late developing areas. The improved weighted relative Theil index and social network analysis are used in this paper to explore the fairness of innovation resource allocation and its spatial correlation features in China’ s eight economic zones from 2011 to 2019. The results show that: (1) There are significant differences in the fairness of regional innovation resource allocation, and obvious ladder levels are existed. (2) The fairness of regional innovation resource allocation continues to improve, which reflects the advantages of regional linkage development. (3) The differences in the regional innovation resource allocation are mainly reflected in the inter-regional differences, and the difference contribution rate of inter-regional differences to the overall differences is continually greater than that of intra-regional differences to the overall differences during the study period. (4) The relative network of the fairness of regional innovation resource allocation has a certain foundation, but its resilience and stability are weak. (5) The fairness of regional innovation resource allocation has a large hierarchical ladder, and the differences are significant.